Peran Guru PAI dalam Memanfaatkan Perpustakaan Sekolah di SMP Takhassus Al-Qur’an Wonosobo - Kholifatun Khasanah; Hanik Laily Rizka Maharani; Khofidhotun Rofingah; Khusna Amalia; Maslakhatul Khulil Laila; Sulastri Sulastri; Tria Taufika; Salis Irvan Fuadi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The school library is a very necessary means by the provider of educational institutions as a material container and resource for teachers and students. Therefore, a good quality library will have a good impact on its students. The purpose of this research is to find out how the role of PAI teachers in using school libraries as a means of learning in SMP TAKHASSUS AL-QUR’AN, knowing the supporting factors and inhibiting factors PAI teacher in using the chool library. This time the research uses qualitative methods, where the method used is not using data but a sentence or a picture, that is, by doing observations, interviews and documentation. As for the results of the research showed that PAI teacher has been very good in performing his role as a teacher in utilizing the school library that is by growing students interest in reading by using the library as a place and means of learning other than in the classroom, giving the student the task to find material to be discussed, read and discussed both in group and individually. As for the constraints in the library only lack of duration, due to PAI lesson hours at the end of the lesson and the majority of students in SMP TAKHASSUS AL-QUR’AN live in the neighborhood of Pondok Pesantren.